1990
DOI: 10.1254/jjp.52.331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gomisin A (TJN-101) on the arachidonic acid cascade in macrophages.

Abstract: Abstract-It has been reported that leukotrienes (LTs) may play a role in inflam matory liver diseases, and several inhibitors of LTs show an inhibitory effect on experimental liver injuries. In this study, the effect of Gomisin A (TJN-101), which is a lignan component of schisandra fruits, on the arachidonic acid cascade in macrophages was examined to explain the mechanisms of the inhibitory effect of TJN-101 on liver injuries. The production of leukotriene B4 was suppressed by treatment with TJN-101, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 19 publications
(27 reference statements)
1
21
0
Order By: Relevance
“…Schizandrin possesses many biological properties (14), including hepatoprotective (15), anti-inflammatory (16), antitumor (17), and antiamnesic effects (18), and a suppressive effect against lipid peroxidation and a potentiating effect on glutathione mediated antioxidation (19). To date, there has been less information concerning its neuroprotective activity against Gluinduced neurotoxicity.…”
Section: +mentioning
confidence: 99%
“…Schizandrin possesses many biological properties (14), including hepatoprotective (15), anti-inflammatory (16), antitumor (17), and antiamnesic effects (18), and a suppressive effect against lipid peroxidation and a potentiating effect on glutathione mediated antioxidation (19). To date, there has been less information concerning its neuroprotective activity against Gluinduced neurotoxicity.…”
Section: +mentioning
confidence: 99%
“…Furthermore, the effect of gomisin A was more inhibitive than those of the inhibitorsof tumor promotion, quercetin [7,14], glycyrrhizin and caffeine [15] against TPA-induced inflammation and tumor promotion. This is the first im portant indication that gomisin A exerts an inhibitory ef fect on the arachidonic acid cascade in macrophages [6], which is observed in inflammation associated with the ac tion of tumor promoters in mouse skin [9], Gomisin A has a little toxic to ICR mice: the LD50 for administration of gomisin A p.o. was 878 mg/kg, and its administration s.c. was 855 mg/kg [Aburada et al, personal commun.].…”
Section: Discussionmentioning
confidence: 83%
“…Gomisin A shows an inhibitory effect against certain types of chemically induced hepatotoxicity [l 5], Gomisin A was found to inhibit the biosynthesis of leukotrienes by preventing the release of arachidonic acid [6]. Lipoxy genase and phospholipase A; inhibitors reduce the degree of 12-O-tetradccanoylphorbol-l 3-acetate (TPA)-induced skin tumor promotion in mice [7 l ()].…”
Section: Introductionmentioning
confidence: 99%
“…Although S. chinensis has many effective compounds regulating brain function, there has been no report regarding the possible anti-neuroinflammatory action. In one study, anti-inflammatory activity of Gomisin A was reported (Yasukawa et al, 1992), but in this case, it was performed in the model of TPA-induced skin tumor formation in mice, and the other two studies were performed in the hepatotoxicity model (Ohkura et al, 1990;Yamada et al, 1993).…”
Section: Discussionmentioning
confidence: 99%